Effects of milk fermented by Lactobacillus helveticus R389 on immune cells associated to mammary glands in normal and a breast cancer model - de Moreno, Maria Alejandra (2005)
Antitumour activity is an effect attributed to probiotics and fermented foods. Here, the immune cells in mammary glands and cytokine concentration in serum were analyzed using mice fed with milk fermented by Lactobacillus helveticus R389 or L89 (proteolytic-deficient variant), injected or not with breast tumour cells. Mice were fed 7 days with fermented milk, injected with breast tumour cells and 4 days post-injection, they received fermented milk. IgA, CD4, CD8, cytokines and Bcl-2 positive cells in mammary glands and cytokine in serum were determined. Mice fed with L. helveticus R389 fermented milk and injected with tumour cells increased IgA and CD4 positive cells in mammary glands (tumour control increased CD8+ cells). Mice from fermented milk control groups (without tumour cell injection) did not show changes in immune cell or cytokine positive cell numbers. IL-10 increases and IL-6 decreases were more pronounced in mice fed with milk fermented by L. helveticus R389 than in the other groups. This study demonstrated the immunoregulatory capacity of milk fermented by L. helveticus R389 on the immune response in mammary glands in presence of a local pathology (breast tumour). Orally administered fermented products could be used to modify the immune cell activation in distant mucosal sites and maintain these cells alert, but local stimulus was necessary to produce the activation of a local immune response in mammary glands, which could modulate the immune-endocrine relationship in these glands.